New insight on carbonisation and graphitisation mechanisms as obtained from a bottom-up analytical approach of X-ray diffraction patterns. (June 2019) - Puech, Pascal; Dabrowska, Agnieszka; Ratel-Ramond, Nicolas; Vignoles, Gérard L.; Monthioux, Marc
Abstract: Extracting average crystallite dimension L a and L c in graphenic carbons from X-ray diffraction (XRD) patterns is wanted because they relate to physical properties, but is complex because of the presence of turbostratic periodicity. We developed a new approach which is physically meaningful regarding both the structural behaviour and the fitting mathematical functions from which L a and L c can be reliably obtained. Thanks to atomistic modelling, and in full agreement with the seminal literature, we found that three basic structural components (BSC) have to be considered for the calculated patterns to fit the experimental ones: (i) the single graphene A, (ii) the graphite stacking (ABA, etc.), (iii) the graphene pair AB. Each of the BSCs may co-exist within the same 00 l -coherent, average, graphenic crystallite, with proportions depend on the carbonisation/graphitisation state. The accuracy of the approach and the availability of new parameters are discussed. The method is applied to the analysis of very distinct XRD patterns from different carbonisation/graphitisation states and mechanisms and is expected to be applicable to all kinds of graphenic carbons. Graphical abstract: The three different Basic Structural Components from the proportions of which any graphenic material can be described, whatever its structural status. Image 1